Research on technology in English education - Young, Carl A.; Kajder, Sara B., 1975- (Emerald Publishing Limited : Information Age Publishing, 2012)
This book brings together the voices of leading English Education researchers who work to offer views into the changing landscape of English as a result of the use of digital media in classrooms, out of school settings, universities and other contexts in which readers and writers work. But, as in most useful texts, the purpose is more nuanced and far reaching than simply offering a glimpse into where we currently find ourselves as a field. In sum, the collection brings together and interweaves what we are coming to know and understand about teaching English within a shifting digital landscape as well as the implications for teacher education and the discipline of English Education specifically.The intended audience for this particular book is English educators, doctoral candidates in the field of English education, researchers and scholars in the field, and English language arts teachers - especially those interested in the impact digital technologies can have in our field.
Keywords: Language arts -- Computer-assisted instruction.; Educational technology -- Research.; Language Arts & Disciplines -- Study & Teaching.; Teaching of a specific subject.; Language teaching and learning.; elektronické knihy; electronic books